Managerial Myopia, Earnings Guidance, and Investment. (3rd November 2022) - Aghamolla, Cyrus; Hashimoto, Tadashi
ABSTRACT: This study investigates the real effects of management communication, specifically of forecasts or earnings guidance, on investment. Managers can signal the strength of their projects through accuracy in their earnings guidance. This leads less accurate managers to distort their investments; the equilibrium investment strategy involves over‐investment when earnings exceed the forecast and under‐investment when earnings fall short. Moreover, we find that managers are pessimistic in their forecasts, which helps to explain the corresponding well‐documented empirical regularity. This downward bias increases the likelihood of investment manipulation but decreases the real loss from distortion. Interestingly, the over‐investment induced by earnings guidance helps to mitigate the classic under‐investment problem for a myopic manager with unobservable investment. Earnings guidance can therefore be value‐increasing when managerial myopia is severe. RÉSUMÉ: Myopie managériale, résultats prévisionnels et investissement Cette étude examine les effets réels de la communication managériale, plus précisément des prévisions ou des résultats prévisionnels, sur l'investissement. Les gestionnaires peuvent signaler la force de leurs projets par la précision de leurs résultats prévisionnels. Cela conduit les gestionnaires qui sont moins précis à créer des distorsions en matière d'investissements; la stratégie d'investissement équilibrée implique un surinvestissement lorsque les résultats se situent au‐dessus des prévisions, et un sous‐investissement lorsque les résultats se situent au‐dessous. De plus, les auteurs constatent que les gestionnaires sont pessimistes dans leurs prévisions, ce qui permet d'expliquer la régularité empirique concordante déjà bien documentée. Ce biais à la baisse augmente la probabilité de manipulation des investissements, mais diminue la perte réelle due à la distorsion. Il est intéressant de noter que le surinvestissement induit par les résultats prévisionnels contribue à atténuer le problème classique de sous‐investissement pour un gestionnaire myope dont l'investissement est inobservable. Les résultats prévisionnels peuvent donc favoriser la croissance de la valeur lorsque la myopie managériale est sévère.